The collected writings of John Maynard Keynes, Volume 11, Economic articles and correspondence - Keynes, John Maynard 1883-1946 (The collected writings of John Maynard Keynes, 2013)
This volume contains Keynes's academic articles and reviews on a number of subjects, as well as his previously unpublished 1909 Adam Smith Prize essay on index numbers. Amongst the subjects covered are India, statistics, World War I and its financing, money and international economics. Included are his papers on the transfer problem, supplemented by related correspondence with Bertil Ohlin